Dimeric peptides of the C‐terminal region of CXCL14 function as CXCL12 inhibitors. Issue 23 (23rd October 2013) - Tanegashima, Kosuke; Tsuji, Kohei; Suzuki, Kenji; Shigenaga, Akira; Otaka, Akira; Hara, Takahiko
Abstract : We recently reported that CXCL14 binds to CXCR4 with high affinity and inhibits CXCL12‐mediated chemotaxis. Here we found that the C‐terminal 51–77 amino acid residues of CXCL14 are responsible for CXCR4 binding. A disulfide dimer peptide of CXCL14(51–77) bound to CXCR4 with comparable affinity to full length CXCL14, and exhibited CXCL12 inhibitor activity. CXCR4 was efficiently internalized upon binding of dimeric CXCL14(51–77), thereby being reduced on the cell surface. Substitution of 5 amino acid residues in combination with the use of an oxime linker for dimerization increased the solubility and chemical stability of the dimeric CXCL14(51–77). Abstract : The C‐terminal 51–77 amino acid residues of CXCL14 are involved in CXCR4 binding. Dimeric peptides of CXCL14(51–77) inhibit CXCL12‐mediated chemotaxis. The oxime dimer of modified CXCL14(51–77) is a chemically stable CXCL12 inhibitor.